Factors Influencing English Language Teachers’ Motivation at Universities - Abdul Sahib, Shahla Mohsin Abdul Sahib (Thi Qar Arts Journal, 2021)
The speaking of the English as a foreign language has expanded remarkably and consequently the demands for learning the foreign language has expanded also .These demands correlate with the motivation to learn the foreign language .The teacher is responsible of the process of higher education ;therefore he might be encouraged and supported .The teacher is the person who transforms the principles of higher education into practical steps and convey them to students in the classroom .The teacher’s encouragement helps to enhance students’ performance and then help students in improving their educational level . Human’s behavior is dominated by the reinforcement principle .People always feel happy when they achieve success and feel sad when they fail . Identifying the motivation is not an easy task , because human behavior is a very complex one . Knowing the kind and the degree of encouragement that suit the English language teachers will be of use for those teachers ,the student and the second language achievement . The main focus of the study will be on identifying the level of support of the English language teachers and the variables that affect that support .